Smart Hydrogel Reactor of Poly(N-isopropylacrylamide)/Polyethylene Glycol Interpenetrating Polymer Networks for Oxidative Coupling of 2-Naphthol - Chen, Minghao; Watanabe, Takumi; Habaue, Shigeki (Synlett, 2023)
Hydrogels with an interpenetrating polymer network (IPN) structure composed of poly(N-isopropylacrylamide) (poly-NIPAM) gel and a gel containing polyethylene glycol (PEG) chains were synthesized. They showed a typical temperature-responsive volume change in water owing to the constructed poly-NIPAM gel component. Oxidative coupling of 2-naphthol with IPN cryogels and a conventional catalyst, the CuCl2 complex of N,N,N′,N′-tetramethylenediamine, was conducted in water under an O2 atmosphere; the IPN gel prepared from PEG with a larger molecular weight of 11000 afforded a product with a good yield of 73% (91% conv.) during the reaction in basic media. The hydrogel effectively promoted the reaction but hardly produced any product without the catalyst, acting as a reactor vessel in the water. Owing to the low durability of the PEG gel component for hydrolysis, a limitation was also suggested during experiments on the recyclability of the hydrogel.
Keywords: interpenetrating polymer networks; hydrogel reactor; smart gel; catalysis; oxidative coupling